The Relationship between Physical Workplace Environment and Employees' Performance / Nur Najihah Erani Hamidi ...[et al.] - Hamidi, Nur Najihah Erani; Mansor, Farah Ahlami; Hashim, Mimi Zazira; Muhammad, Norrini; Wan Azib, Wan Nor Hazimah (Universiti Teknologi MARA Cawangan Kelantan, 2020)
In today’s dynamic and competitive business world, a healthy workplace environment makes good business sense. Managers should not just focus on the employees’ salary to enhance employees’ performance as there are many other factors that need to be considered. Organization which is perceived as a positive place to work will relatively yield a competitive edge. In this study, the researchers focused on the relationship between physical workplace environment and employees’ performance. Several factors of physical workplace environment have been identified by the researchers, namely the office layout, lighting, furniture and equipment of the workplace. Physical office environments may influence the office employees’ well beings where they spend long hours inside the office building. Employees who are well-equipped with workplace environmental support will be highly satisfied and show high level of commitment towards their organization. Better physical workplace environment will boost employees’ performance. Employees are the backbone of any organizations. Employees are influenced to deliver their best performance depending on how well their work environment is. Committed employees who are highly motivated by conducive work environment synergise their time and energy in the pursuit of achieving organizational goals. Therefore, this paper will determine the relationship between physical workplace environment and employees’ performance at government agency in Kedah. Questionnaires was distributed to 100 respondents as the sample size for this study from the total population of 140 employees of different departments and units. The finding of this paper revealed that the lightings is the most leading factor of physical workplace environment that affect the performance of employees. Therefore, the recommendation for this study focused most on the factors of lighting options that can be used by the organization